posted by .

f(x)=7x^3+13x^3-3x^2. Find f(-6)
Also how do you solve this kind of question

  • Math -

    notice that in the place of x in f(x) you now find a -6
    so in the expression , replace x with -6 as well

    f(x) = 7x^3+13x^3-3x^2
    f(-6) = 7(-6)^3 + 13(-6)^3 - 3(-6)^2
    = ...

    I suspect a typo, why would you have two different cubic terms ?

  • Math -

    So for this kind of question. You just replace the variables right?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    can someone show me the steps for this problem because i got it incorrect in my exam. Solve each of the following quadratic equations. 4x^2=13x+12 what i had put was that x is 3/4 and x is -4 but i just got my result back and it was …
  2. Algebra

    Can you pleas Solve the quadric equation step by step 4x square =13x+2 4x^2 = 13x + 2 subtract 13x and 2 from both sides 4x^2 - 13x - 2 = 0 Now use the quadratic formula, since it does not factor.
  3. math/algebra

    subtract. express in simplest form 13x/30 - 4x/ 15 = factor the first denominator. Get a common denominator. Combine terms. I will be happy to critique your work. ok 13x/30 - 4x/ 15 = This is where I get lost, I know that I have to …
  4. Algebra

    Hello all - I would like to check my work on 2 problems. Solve by factoring : x^2-13x= -12 x^2-13x+12= -12 + 12 x^2-13x+12= 0 (x-1)(x-12)= 0 x = 1 , 12 Solve using the square root property: 2x^2-35=15 2x^2-35-15=0 2x^2-50=0 2(x-5)(x+5)=0 …
  5. intermidate algebra

    Solve each equadratic equation by factoring. 6^2-13x-28 36-13x-28 -13x=-36+28 x=64/13 check this, correct if wrong
  6. Math

    Solve the following equation. 4.7 = 1.13x^2 Do i square root the 1.13x^2 first?
  7. Math

    I know that I posted this already but my question has not been answered.. Solve in the exact form. Original problem: (sqrt of 4x+1)+(sqrt of x+1)=2 4x+1 + 2√(4x^2+13x+3) + x+3 = 4 Where does the 2 come from according to the equation …
  8. Math

    My work on simplifying this function: g(x)=(-3x^2-13x-13) g(x)=-3x^2-13x-13 (13x-13=x) g(x)=-3x^2-x Can someone help with the simplifying the function if I have got it wrong and also can someone tell me of it's equivalent to this function:f(x)=-3(x+2)^2-(x+1) …
  9. Math last question.

    (3x^2 - 7x -4) - (6x^2 -6x +1) It's a polynomial I think the answer is D or C, but I'm not sure which one. Help please A. 3x^2 - 13x - 5 B. 9x^2 - x + 5 C. -3x^2 -13x + 5 D. -3x^2 -x -5
  10. math practice help

    add or subtract (2x^2+6x+1)+(-7x^2+2x-3) 5x^2-4x-2 -5x^2+8x-2 5x^2-8x+2 -9x^2-8x+2 (3x^2-7x-4)-(6x^2-6x+1) -3x^2-x-5 -3x^2-13x+5 9x^2-x+5 3x^2-13x-5 These are just practice problems. could someone help me figure out how to solve them …

More Similar Questions